La memoria histórica como herramienta pedagógica para la enseñanza del conflicto armado colombiano (2021)
This document represents a compilation monograph which brings together a series of research and documents that relate and express how historical memory is used to understand the armed conflict in education and more precisely in the social sciences, for this purpose a detailed analysis is made from the qualitative paradigm which allows understanding the social reality, in this case of the armed conflict through historical memory, an analysis of sources was made, from there certain categories of analysis were identified such as: historical memory, armed conflict and peace professorship, these were selected after identifying their continuous presence in the different written documents.